2001
DOI: 10.1111/j.2042-7174.2001.tb01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient self-eports of potential adverse drug reactions

Abstract: Focal points □ A systematic questionnaire was found to be a feasible method of facilitating patients to report symptoms they perceived to be potential adverse effects of drugs □ Although 89 per cent of patients who had taken tramadol and venlafaxine reported at least one symptom in questionnaires, only 58 per cent of these claimed to have reported their symptoms to their doctor □ Only 22 per cent of symptoms reported by a sample of patients were found to be recorded in medical records and only 23 yellow card r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our findings are consistent with those from other studies. For example, Krska et al (2001) found that 89% of patients taking either tramadol or venlafaxine reported at least one ADR. Only 58% of these patients reported the ADR to their general practitioner, and only 22% of the ADRs were documented in the patient's casenotes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those from other studies. For example, Krska et al (2001) found that 89% of patients taking either tramadol or venlafaxine reported at least one ADR. Only 58% of these patients reported the ADR to their general practitioner, and only 22% of the ADRs were documented in the patient's casenotes.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similar results comparing spontaneous reporting of ADRs with other methods have been reported. 22 Although the time periods were different in that the calculated ADR rate for spontaneous reporting was based on 2004 data, a similar rate was reported to CARM in 2005. 15 There is an association between the number of medicines being taken and the risk of experiencing an ADR.…”
Section: Discussionmentioning
confidence: 91%
“…This leads to taking a decision to do an intervention of a new health care teamwork approach with an intention to complete patient care during ATT with a special preference on ADR reporting system. The evidence of patient's definite role in ADR and their willingness to report the ADR [22][23][24][25] were planned to utilize in this study by expecting a good adherence. Here comes the importance of pharmaceutical care based approach to the TB patient.…”
Section: Introductionmentioning
confidence: 99%